2012
DOI: 10.1016/j.neuropsychologia.2012.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating Thatcherised from typical faces in a case of prosopagnosia

Abstract: We report data from a prosopagnosic patient (PHD), and aged-matched control participants, from experiments where participants categorised individually presented emotional faces (experiment 1) and Thatcherised (from typical) faces (experiment 2). In experiment 2 participants also discriminated between simultaneously presented Thatcherised and typical faces. PHD was at chance categorising Thatcherised from typical faces. He was, however, able to discriminate between Thatcherised and typical faces, and partially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…A number of investigations have also revealed deficits in the processing of complex familiar and novel objects, and the extent of these impairments is linked to the severity of the reading disorder (e.g., Behrmann et al., 1998a , Cumming et al., 2006 , Mycroft et al., 2009 ). This work extends initial observations of face processing deficits in patients with left pFG lesions (e.g., Behrmann and Plaut, 2013a , Mestry et al., 2012 , Roberts et al., 2013 ) by establishing that these deficits extend across familiar and novel stimuli, and relate to the visual processing requirements of the novel faces in terms of the involvement of featural and configural processing.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…A number of investigations have also revealed deficits in the processing of complex familiar and novel objects, and the extent of these impairments is linked to the severity of the reading disorder (e.g., Behrmann et al., 1998a , Cumming et al., 2006 , Mycroft et al., 2009 ). This work extends initial observations of face processing deficits in patients with left pFG lesions (e.g., Behrmann and Plaut, 2013a , Mestry et al., 2012 , Roberts et al., 2013 ) by establishing that these deficits extend across familiar and novel stimuli, and relate to the visual processing requirements of the novel faces in terms of the involvement of featural and configural processing.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, a number of functional neuroimaging studies have found overlapping activations in left pFG for words and faces ( Hasson et al., 2002 , Kveraga et al., 2007 , Mei et al., 2010 , Vogel et al., 2012 , Woodhead et al., 2011 ), with some even revealing overlap at the voxel level ( Nestor et al., 2013 ). In addition, although face identification deficits are commonly associated with damage to the right pFG, including the fusiform face area (FFA), these are worse in cases of bilateral damage ( Barton, 2008 ), indicating a contribution of left pFG as well ( Mestry, Donnelly, Menneer, & McCarthy, 2012 ). We would therefore expect to see evidence of face processing deficits in patients with left pFG damage, despite the functional preservation of right hemisphere occipito-temporal regions implicated in face processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Critically, an interaction of orientation and eye Thatcherisation was found for the P3b amplitude. Results from an individual with acquired prosopagnosia who can discriminate Thatcherised from typical faces but cannot categorise them or perceive the illusion (Mestry, Donnelly et al in Neuropsychologia, 50, 3410-3418, 2012 ) only differed from typical participants at the P3b component. Findings suggest the P3b links most directly to the experience of the illusion.…”
mentioning
confidence: 98%
“…We also tested PHD, an individual with acquired prosopagnosia. PHD has no N170 face effect (Eimer & McCarthy, 1999 ) and is unable to categorise individual faces as Thatcherised or typical, but is able to make same/different judgements to simultaneously presented pairs of Thatcherised and typical faces (Mestry, Donnelly, Menneer & McCarthy, 2012 ). We tested PHD to explore which markers present in the ERP traces of typical participants would disappear for PHD in the absence of sensitivity to the illusion.…”
mentioning
confidence: 99%